The functions of spin on short trajectory in table tennis - Kusubori, S.; Yoshida, K.; Sekiya, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine the function of spin on shot trajectory during flight in table tennis. Using film images of an actual match, we computed the 3D coordinates of a ball to analyze the shot trajectories. The theoretical spin-free (TSF) ball trajectories, obtained using a similar approach to Jinji and Sakurai (2006), were compared with the observed shot trajectories. For drive shots, the shot length in the TSF ball was significantly longer than in the observed shots. However, for push shots, among the 30 shots analyzed, 17 of the TSF balls traveled a shorter distance than the observed shots, though difference between them was found not to be significant. The work done by Magnus effect on the ball was estimated by the amount of deflection in vertical direction during flight.